"If the Spirit of the Original Is to Be Retained": Ways of Seeing Camerawork - Samuel Bibby (British Art Studies)
For perhaps as long as they have been the focus of scholarly attention, periodicals as objects have always posed a challenge to those trying to convey their understanding of them to an audience, be it in the three-dimensional space of a museum display or in the two-dimensional context of a photographic reproduction printed on a page. Conventionally, in each instance only a single opening---two facing pages of a magazine---can be presented to the viewer at any one time, a condition determined by the physical nature of the codex format: the bind of the bound. Charting the range of strategies that have been employed to try to overcome---or at least compensate for---this furnishes us with the chance to reflect on what producing periodicals means today, both as a historical subject and as a contemporary practice. As part of this historiographical endeavour, the intersection of the fields of periodical studies and digital humanities provides a useful opportunity to think through the various questions that such printed material engenders. How were periodicals used in the past? How are those same periodicals used today? And how are they employed now to understand how they were then? How too might such layers of use (and meaning) be captured and conveyed? In this article I seek to address such issues through looking at a single case study, the photographic magazine *Camerawork*, which was produced in Britain between 1976 and 1985 by members of the Half Moon Photography Workshop.